Cash Transfers and Child Schooling Evidence from a Randomized Evaluation of the Role of Conditionality - Akresh, Richard (The World Bank, 2013)
The authors conduct a randomized experiment in rural Burkina Faso to estimate the impact of alternative cash transfer delivery mechanisms on education. The two-year pilot program randomly distributed cash transfers that were either conditional or unconditional. Families under the conditional schemes were required to have their children ages 7-15 enrolled in school and attending classes regularly. There were no such requirements under the unconditional programs. The results indicate that unconditional and conditional cash transfer programs have a similar impact increasing the enrollment of children who are traditionally favored by parents for school participation, including boys, older children, and higher ability children. However, the conditional transfers are significantly more effective than the unconditional transfers in improving the enrollment of "marginal children" who are initially less likely to go to school, such as girls, younger children, and lower ability children. Thus, conditionality plays a critical role in benefiting children who are less likely to receive investments from their parents